Variation of Bulk Modulus, Its First Pressure Derivative, and Thermal Expansion Coefficient with Applied High Hydrostatic Pressure - Manaf A. Mahammed; Hamsa B. Mohammed (Advances in Condensed Matter Physics)
Throughout this work, the equations of variation of the isothermal bulk modulus, its first pressure derivative, and the volumetric thermal expansion coefficient as a function of pressure were derived based on the Birch–Murnaghan equation of state (B–M EOS). The bulk modulus and its first derivative at ambient temperature for nine elements were extracted by fitting the published experimental pressure–volume data to B–M EOS, and the results were compared with other published researches, and there was a good agreement. Moreover, those extracted values were used to study the variation of the isothermal bulk modulus, its first pressure derivative, and the isothermal coefficient of thermal expansion as a function of the applied hydrostatic pressure using the equations that were derived from this work.